Letter to the editor of the Brit J Clin Pharmacol on Hartjes et al. 2025 https://doi.org/10.1002/bcp.70176 - Rafael Henry‐Venson (British Journal of Clinical Pharmacology, 2025)
OBJECTIVES: This study aims to evaluate the immunomodulatory effects of an 808 nm laser therapy on human primary natural killer (NK) cells. METHODS: We assessed NK cell viability, apoptosis, ATP and ROS production, cytotoxicity against target cells, and the expression of functional receptors and cytokines following irradiation with an 808 nm laser in vitro. Furthermore, a laser-irradiated mouse model was used for in vivo studies. For the cell experiments, the irradiation parameters were set at 200 mW and 21 mW/cm2. In the mouse model, cells were irradiated at 10 J/cm2 for 60 s every other day over a 2-week period. RESULTS: The results showed that 808 nm laser photobiomodulation did not induce significant apoptosis in human NK cells after continuous irradiation. Laser irradiation increased intracellular ROS and ATP levels in human NK cells and altered ROS levels in mouse peripheral blood cells. In vitro experiments further demonstrated increased NK cell-associated cytotoxic responses, accompanied by elevated expression of NKG2D and enhanced degranulation-related signals. In vivo analyses revealed altered proportions of lymphocytes, neutrophils, and NK cell-associated populations in mouse peripheral blood following laser irradiation. In addition, serum CXCL1 and IL-12p40 levels were decreased in mice after laser treatment, suggesting potential modulation of systemic inflammatory responses. Furthermore, altered expression of JNK, PI3K, and p38 signaling proteins was observed in mouse peripheral blood leukocytes following laser irradiation. CONCLUSIONS: This study demonstrated that 808 nm laser photobiomodulation was associated with immunomodulatory alterations in human NK cells in vitro and systemic immune-related responses in vivo. These findings provide preliminary experimental evidence supporting the potential immunomodulatory application value of 808 nm laser photobiomodulation.